The Effect of The Application of The Mind Mapping Learning Model to Improve The Critical Thinking Ability of Elementary School Students in Tanggulangin - Aulya Firda Trisnawati; Akhtim Wahyuni (STAI Hubbulwathan Duri, 2022)
Thematic learning in the 2013 curriculum requires students to be more active and think critically. The ability to think critically is essential for students, especially facing the challenges of the 4.0 era. In reality, the elementary school students in Tanggulangin cannot yet think critically. Most students answer essay questions without being able to describe them in detail. This study was conducted to analyze how the application and results of the mind mapping learning model improve students' critical thinking skills. The research method used is the class action research method. The object of his research was a grade V student of the Elementary School in Tanggulangin. The techniques used in this study are observation and test techniques. The results showed: (1) The application of the mind mapping learning model to improve students' critical thinking skills was carried out in 4 stages compiling an Action design, applying a mind mapping learning model, observing the results obtained from the application of the mind mapping model and evaluation. (2) The results of the mind mapping learning model show that the percentage of students' critical thinking ability with mind mapping media has increased from cycle 1 to cycle two by 24.15%. Further research is expected to be carried out with diverse respondents, with more than two-cycle stages, to analyze the percentage of the graph produced more significantly